Clinical Spectrum of Orbital Cellulitis: Case Series From Subperiosteal Abscess to Life-Threatening Cavernous Sinus Thrombosis - Putri Amanda; Havriza Vitresia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Orbital cellulitis encompasses a range of orbital infections with varying severity. This case series highlights the diverse clinical presentations, management strategies, and outcomes of orbital cellulitis, emphasizing the importance of prompt diagnosis and treatment. Case presentation: We present two cases of orbital cellulitis with contrasting presentations. The first case involved a 16-year-old male with acute rhinosinusitis who developed severe orbital cellulitis complicated by cavernous sinus thrombosis (CST), requiring aggressive medical and surgical interventions. The second case involved a 2-month-old female with a subperiosteal abscess secondary to ethmoid and maxillary sinusitis, who responded well to medical management alone. Conclusion: Orbital cellulitis presents a wide spectrum of clinical scenarios, ranging from localized infections to life-threatening intracranial involvement. Early recognition, appropriate imaging, and timely intervention are crucial for optimizing outcomes. While CST necessitates aggressive measures, subperiosteal abscesses can often be managed medically, particularly in young children.